Women's Body Capital in The Modern Fashion World - Yovita Devi; Deny Tri Ardiyanto; Marimin Marimin (International Journal of Science and Applied Science: Conference Series, 2022)
The body of women in the modern fashion world is now not only present in the form of a subject, but also becomes an object. The female body has become a very exploitative realm for the modern fashion world. The movement as a tool to dismantle the old interpretation of something that is unfair because of the patriarchal culture, is the feminism movement. Women are still discriminated against and do not have the same rights as men for their private bodies. The awareness that women have today is a false consciousness, which in practice makes women feel ownership of their own bodies, can proudly show off their curves during fashion shows, photoshoots and so on. In fact, there is no awareness at all, what is protected here are not people who are proud to show off their bodies, no. However, what is defended from this research is the bodies of women so that there are no sexual crimes that are accepted by women. The data obtained were then processed with a qualitative descriptive approach with the subject of this study being the female body capital in the world of modern fashion. The theory used is the theory of Marxist feminism. The research uses hermeneutics which will interpret, provide understanding, and translate the capital of the female body in the world of modern fashion. While the validity of the data with data triangulation as a technique of checking the validity of the data that utilizes something other than the data for the purpose of checking or comparing the data.